Dye adsorption and bactericidal properties of TiO2/chitosan coating layer. (5th September 2016) - Kamal, Tahseen; Anwar, Yasir; Khan, Sher Bahadar; Chani, Muhammad Tariq Saeed; Asiri, Abdullah M.
Highlights: TiO2 /chitosan coating layer was used for thymol violet dye removal from water. The adsorption capacity of TiO2 /chitosan coated cellulose microfibers was 97.51 mg g-1. Efficient antibacterial performance by composite coated cellulose against E. coli . Abstract: A new kind of titanium oxide dispersed in chitosan (TiO2 /CS) nanocomposite adsorbent was prepared and adhered to high surface area substrate, cellulose microfibers mat (CMM). CS-CMM and TiO2 /CS-CMM were used for the thymol violet (TV) dye removal from wastewater. Characterization of materials was carried out by X-ray diffraction, scanning electron microscope and energy dispersive X-ray spectroscopy. The adsorption properties of both the CS-CMM and TiO2 /CS-CMM were investigated as a function of adsorbent dosage, solution pH, and contact time. It was revealed that the composites pretreated in the solution with higher pH value exhibited larger adsorption capacities. Kinetic studies showed that the composites could adsorb TV dye rapidly and reached the equilibrium in 90 min. The adsorption process followed pseudo-second order kinetics and involved particle diffusion mechanism. The calculated maximum adsorption capacities of CS-CMM and TiO2 /CS-CMM were 84.32 and 97.51 mg g −1, respectively. Compare to CS, the TiO2 /CS nanocomposite coated CMM showed higher antibacterial characteristics as tested against Escherichia coli .